Self-assessment exercises in continuum mechanics with autonomous learning - Jordi Marce-Nogue; Lluis Gil; Marco A. Pérez; Montserrat Sánchez (OmniaScience, 2013)
The main objective of this work is the generation of a set of exercises to improve the autonomous learning in "Continuum Mechanics" through a virtual platform. Students will have to realize four exercises autonomously in relation to the subject matter developed in classes and deliver the solutions of each problem via the virtual platform within a deadline. Students must do a self-correction of the exercises and assign the mark that corresponds according to a criterion of a rubric designed by teachers.